(untitled) (Eurasian Medical Research Periodical, 2022)
Escherichia coli is a Gram-negative, rod-shaped bacterium that belongs to the Enterobacteriaceae family and the Gammaproteobacteria class. E. coli is one of the most prevalent organisms that cause bacterial illnesses. Globally, the rise of multidrugresistant E. coli poses a significant risk to public health. Antimicrobial resistance in E. coli is causing havoc in the world’s healthcare system Aim this study: The goal of this study was to find out how resistant clinical isolates of E. coli were to antibiotics